Learning Logical Lessons from Stories - Becker Arenhart, Jonas (Logic and Logical Philosophy, 2025)
TThat stories may teach us some important lessons, e.g. about morals, is not new; what is a recent topic of discussion, however, is whether stories can be equally useful for logic. Can we learn something valuable about logical validity from stories? We address this problem in this paper. We first examine two opposing positions on that matter, with a positive and a negative answer to the question of whether stories may teach us something about logic. We shall then suggest that those positions both labor under the assumption that logic has a descriptive role aiming to correctly describing validity simpliciter. We argue that as a result of the use of stories in logic, such an assumption must be abandoned in favor of a more local view of logical consequence. The view makes sense of the use of stories in logic, and also accommodates the claim that the plurality of stories may be seen as leading us to no universally applicable logic at all.